Association Between Glycosylated Hemoglobin and Cardiovascular Events and Mortality in Older Adults without Diabetes Mellitus in the General Population: The Leiden 85‐Plus Study. Issue 6 (1st June 2015) - Birkenhäger‐Gillesse, Elizabeth G.; den Elzen, Wendy P. J.; Achterberg, Wilco P.; Mooijaart, Simon P.; Gussekloo, Jacobijn; de Craen, Anton J. M.
<x xml:space="preserve">Abstract</x> Objectives To examine the association between glycosylated hemoglobin (HbA1c) and incident cardiovascular disease and mortality in 85‐year‐old individuals without diabetes mellitus from the general population. Design Population‐based prospective follow‐up study. Setting General population. Participants Individuals without known diabetes mellitus (N = 445, n = 291 female). Measurements HbA1c levels were categorized into three groups (<5.0% (31 mmol/mol), 5.0–5.7% (31–39 mmol/mol; reference), 5.7–6.5% (39–48 mmol/mol)). Results At baseline, a history of myocardial infarction (MI) was more prevalent in subjects in the highest HbA1c group (18%) than in the reference group (7%) (P = .001). Prospectively, those with the highest level of HbA1c at baseline had a risk of incident MI during the 5‐year follow‐up that was 3.6 (95% confidence interval = 1.5–8.3) times as great as that of the reference group. No association was found between HbA1c level and incident stroke, cardiovascular mortality, or all‐cause mortality. Conclusion In individuals aged 85 and older without diabetes mellitus, higher HbA1c is associated with greater risk of MI but not with stroke and mortality.